Indonesian Journal of Obstetric and Gynecology=Majalah Obstetri dan Ginekologi Indonesia, Vol.2 No.3 Halaman 115-172, July 2014 - Perkumpulan Obstetri Dan Ginekologi Indonesia (POGI, 2014)
Social Support and Postpartum Depression in Human Immuno Deficiency Virus (HIV) Patients Changes of Body Mass Index and Lipid Profile in Injectable Depo Medroxyprogesteron Acetate and Levonorgestrel Implant Acceptors Profile of Estrogen Metabolism in Endometriosis Patients Hang-up IUD, New Technique for Suturing CuT-380A IUD to Uterine Fundus in Immediate Postplacental Insertion during Cesarean Delivery: Twelve Months Follow up Impact of Uterine Prolapse Surgery on Improvement of Bowel Symptoms Recurrence-Free Survival Stage iB1-IIA2 Intermediate Risk Group (Based on Kartu Delgado) Cervical Carcinoma After Radical Surgery and Adjuvant Radiotherapy Prevalence of High-Risk Human Papillomavirus (HPV) among Negative Visual Inspection of Acetic Acid (VIA) Ovarian Malignancy Prediction by Gatot Purwoto (GP) Score, Risk Malignancy Index (RMI), and Frozen Section in Young Age